Inhibiting Factors in Coastal Wastel Management in Lawanga Tawongan Sub-District, North Poso City District - Muh Saiful Darsono; Nggilu, Rukiah; Djaba, Misbahudin (Science Tech Group, 2025)
This study aims to identify and analyze the inhibiting factors in coastal waste management in Lawanga Tawongan Sub-district, North Poso City District, Poso Regency. The method used is descriptive qualitative with three main focuses: Facilities, Public Awareness, and Supervision. Data sources were obtained through interviews, observations, and documentation, with primary and secondary data serving as references for analysis. The research findings indicate that facility-related issues are the main obstacles, marked by the limited number of Temporary Disposal Sites (TPS), the lack of waste collection vehicles, and the unequal distribution of trash bins in strategic locations. Public awareness regarding coastal cleanliness remains low, as reflected in the habit of littering and the lack of participation in cleanup activities. Furthermore, supervision from the sub-district government has not been optimal due to the absence of clear regulations or strict sanctions, as well as the lack of a community-based monitoring system. These conditions hinder the effectiveness of waste management efforts. Therefore, an integrated strategy is needed, including infrastructure improvement, environmental education, and the establishment of community-based regulations and supervision.